Respostas
respondido por:
4
a10=a1+9r
a1+6r = -7 (-1)
a1+9r = -5
¨¨¨¨¨¨¨¨¨¨¨¨¨¨
-a1 -6r = 7
a1 +9r = -5
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
........3r = 2
..........r = 2/3
a1 + 6r = -7
a1 + 6.2/3 = -7
a1 + 4 = -7
a1 = -7-4
a1 = -11
a1+6r = -7 (-1)
a1+9r = -5
¨¨¨¨¨¨¨¨¨¨¨¨¨¨
-a1 -6r = 7
a1 +9r = -5
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
........3r = 2
..........r = 2/3
a1 + 6r = -7
a1 + 6.2/3 = -7
a1 + 4 = -7
a1 = -7-4
a1 = -11
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás